(untitled) (Scientific journal of the Fergana State University, 2025)
A new political and philosophical worldview formed in our country during the years of national independence, along with the recognition that “high spirituality is the basis of the development of society", “spirituality", “value", “culture", “man", “perfect man", “civil society", “civilization”, “civilized progress”, such universal and philosophical concepts as “the rule of law”, “private property”, “human rights”, “individual freedoms” began to serve as a methodological basis, a scientific paradigm in a new understanding of the essence. This article examines the philosophical aspects of strengthening the foundations of national statehood and building a civil society.